Developing a Mathematical Literacy Learning Environment for Students through Educational Game Assistance - Hamidah, Ida; Zulkardi; Putri, Ratu Ilma Indra; Pramuditya, Surya Amami (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Mathematical literacy is a fundamental skill that enables students to solve real-life problems, think critically, and make informed decisions across various contexts. Its absence can impede students' academic success and limit their ability to address challenges in a technology-driven world, underscoring the importance of this research in enhancing their future opportunities. A significant factor contributing to this issue is the inadequate implementation of teaching practices that support mathematical literacy in schools. To address this challenge, this study aims to develop a valid, practical, and impactful mathematical literacy learning environment for junior high school students using educational game assistance. A design research method with a developmental research approach was employed, consisting of three stages: the preliminary stage, prototype development, and evaluation. The data were analyzed through qualitative descriptive analysis. This study developed a mathematical literacy learning environment leveraging educational game technology to enhance student learning. The environment was validated in terms of content, construct, and language aspects, deemed practical for its ease of use, accessibility, flexibility, and alignment with learning objectives, and evaluated for its potential impact based on Guskey's five-levels framework. The results highlight its potential impact on improving mathematical literacy and addressing the challenges posed by inadequate teaching practices in schools. This research underscores the importance of integrating innovative educational tools to better prepare students for success in a technology-driven world.